Ethical dilemmas in the development of college psychological counseling under the background of cultural integration - Xing, Wei; Zheng, Yanan (Frontiers in Psychology, 2025)
A discernible change in the ideological stances of college students has coincided with the growing occurrence of cultural integration in China. At the same time, mental health concerns in higher education have become more prevalent and demand scholarly attention. Inadequate multicultural competency among counselors, unclear professional identity delineation, and inter-regional differences in development are some of the issues facing the current psychological counseling system in higher education institutions that demand immediate attention. Additionally, integrating cultures may require resolving moral conundrums involving principles of value neutrality and confidentiality, among others, which jeopardize the development and upkeep of consultation relationships. To improve the current situation, efforts should be made to enrich the professional guidance and multicultural experience of college counselors, so as to make college psychological counseling adapt to the development and changes of the current situation.